Road Congestion Pricing: A Case Study Analysis of the Ambiguity and Evolution of Policy Objectives - webster, jordan. (Tufts University. Tisch Library., 2020)
Thesis (M.S.)--Tufts University, 2020.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Justin Hollander.; Committee: Shan Jiang.; Keywords: Transportation, Sustainability, and Economics.